Design of an in-situ measurement system for ortho and para liquid hydrogen fractions at ESS. Issue 1 (1st May 2022) - Tatsumoto, H; Lyngh, D; Lee, Y; Hartl, M; Sina, H; Arnold, P; Beßler, Y; Kobayashi, H; Sakamoto, Y; Hasegawa, T
Abstract: The Cryogenic Moderator System (CMS) is equipped with a catalyst to convert hydrogen from the ortho state to the para state, to keep desirably high parahydrogen fractions in the cold moderators, which is required to deliver a high brightness cold neutron beams to the scientific instruments using neutron scattering. An in-situ measurement system for the ortho and para fractions of liquid hydrogen (OPMS) where a Raman spectroscopy will be used is being developed. The required measurement precision is 0.1% to detect an undesirable shift towards a high orthohydrogen fraction caused by neutron scattering driven para-to-ortho back conversion. The dedicated OPMS sampling line has been designed and is placed in a bypass line from and to the CMS to minimize the hydrogen inventory and to make it physically isolated from the CMS if a sapphire window failure happens. Accident analysis for a hydrogen leak due to the sapphire window failure was carried out using an inhouse-developed simulation code, and the required safety relief size has been determined.